Universidade Federal de Rondônia (UNIR): desafios e enfrentamentos na constituição de uma instituição universitária multicampi - Moreira, Dorosnil Alves (2005)
This research sought to describe and analyse how the Universidade Federal de Rondônia (UNIR) took form as a multicampi university institution between 1982 and 2002. For this purpose we perused the stiff authority relationship between the university institution and its vicinities. Upon contemplating the interests of groups present therein I sought to record the public policies, reforms and enterprises within UNIR and its respective entailment in the cities and in respect of the subjects involved therewith. Having chosen a qualitative approach, the research techniques included surveys, forms and documents pursuant to the process of interiorization of this university. The subjects inherent in the survey were former dwellers, academic community members, visiting professors, graduates, former professors and leading members of the cities of the Estate of Rondônia. The theoretical reference that grounded our analyses encompassed scholars involved with social, university, public policies, educational and social economic issues, in the critic, future and social emancipation sphere, amongst which we may quote Chizzotti, Dowbor, Wanderley, Freire, Ianni and Morais. The ensuing results evidence a process of interiorization of this university as a set of public policies applied to the constitution of a multicampi institution, arising from the aggregation of articulations of politics and local practices that found in the social realm mechanisms for production and reproduction of knowledge sources of conformation and contention. Such mechanisms were stirred up and propelled by means of the articulation of disperse potentialities, in and out of the institution, that, organized through the university institution, made it possible to endure and overcome the deadlocks and challenges aiming at meeting the thorough social needs and the local and regional development. Clearing the constituting elements of the multicampi institution revealed temporal limits to individual interests collectively manifested and the likelihood of articulation of individual interests for an including future grounded on ethic precepts. An example of subsidence and illustration of challenges and confrontations seen at UNIR (1982-2002) this research spoke for subjects of this process, recovering documents and presenting a multicampi university on course of constitution, pointing out its historical roots and projects of consolidation